Kinetics of Colonization of Adult Queensland Fruit Flies (Bactrocera tryoni) by Dinitrogen-Fixing Alimentary Tract Bacteria - Murphy, Kathleen M. (1994)
The average total population of bacteria remained constant in the alimentary tracts of adult laboratory-raised Queensland fruit flies (Bactrocera tryoni) although the insects had ingested large numbers of live bacteria as part of their diet. The mean number of bacteria (about 13 million) present in the gut of the insects from 12 to 55 days after emergence was not significantly modified when, at 5 days after emergence, the flies were fed antibiotic-resistant bacteria belonging to two species commonly isolated from the gut of field-collected B. tryoni. Flies were fed one marked dinitrogen-fixing strain each of either Klebsiella oxytoca or Enterobacter cloacae, and the gastrointestinal tracts of fed flies were shown to be colonized within 7 days by antibiotic-resistant isolates of K. oxytoca but not E. cloacae. The composition of the microbial population also appeared to be stable in that the distribution and frequency of bacterial taxa among individual flies exhibited similar patterns whether or not the flies had been bacteria fed. Isolates of either E. cloacae or K. oxytoca, constituting 70% of the total numbers, were usually dominant, with oxidative species including pseudomonads forming the balance of the population. Antibiotic-resistant bacteria could be spread from one cage of flies to the adjacent surfaces of a second cage within a few days and had reached a control group several meters distant by 3 weeks. Restriction of marked bacteria to the population of one in five flies sampled from the control group over the next 30 days suggested that the bacterial population in the gut of the insect was susceptible to alteration in the first week after emergence but that thereafter it entered a steady state and was less likely to be perturbed by the introduction of newly encountered strains. All populations sampled, including controls, included at least one isolate of the dinitrogen-fixing family Enterobacteriaceae; many were distinct from the marked strains fed to the flies. Nitrogenase activity detected by the acetylene reduction assay was associated with flies fed dinitrogen-fixing bacteria as well as with control groups given either no supplement or free access to a yeast hydrolysate preparation. Nitrogen fixed from the atmosphere may supplement the nutrition of the alimentary tract microbial population of B. tryoni. Transmission electron microscopy showed that the principal site of bacterial colonization in the abdominal alimentary tract was the lumen of the midgut inside the peritrophic membrane. No intracellular symbionts were seen in the gut tissues nor were bacteria found attached to the cuticular folds of the hindgut. The ultrastructure of the gut resembled that of other fly genera except that the intercellular spaces between rectal epithelial cells were more extensive, suggesting a role for unspecialized epithelium in water and solute uptake in B. tryoni.